Readability of Online Sources Regarding Meniscal Tears - Hodax, Jonathan D.; Baird, Grayson L.; McBride, Trevor; Owens, Brett D. (The Journal of Knee Surgery, 2017)
Meniscal injuries are extremely common, with an incidence of 8.3 per 1,000 person/years in young, active individuals. Patients often turn to the internet to glean information about their injuries, and even to guide decision making about treatment. Much research has been done demonstrating that a reading level of eighth grade or lower is appropriate for accurately communicating written information to patients, yet medical practitioners often fail to meet this requirement. To better examine the information patients receive about meniscal injuries, we set out to evaluate the reading level and content of three commonly used search terms on the three search engines with the largest market share. The authors examined the keywords “meniscus tear,” “meniscus tear treatment,” and “knee pain meniscus” on the three highest market share search engines. The top 10 results from each search were included, and redundancies identified. Unique Web sites were evaluated for source, word count, reading level, and content including advertisements, diagrams, photographs, nonoperative and operative options, and accurate medical information. A total of 23 unique Web sites were identified in our search, including 13 public education sources, 6 academic institutions, and 4 private physicians/groups. Average grade levels of articles ranged from 9.4 to 14.2 (mean, 11.14; standard deviation [SD] 1.46), and Flesch–Kincaid reading ease scores ranged from 23.9 to 68.7 (mean, 55.31; SD, 10.11). Pages from public sources required the highest level of readability (11.6, 95% confidence interval [CI]: 9.8–13.2), which was significantly higher than private (11.0, 95% CI: 9.3, 12.7]) and academic (10.9, 95% CI: 8.9–12.9), p = 0.007 and p = 0.002, respectively. Further efforts to make appropriate health information available to patients are needed.
Keywords: meniscus; readability; patient communication